Does local resistance impact the transnational normative environment? The case of female genital mutilation (FGM) - Oztig, Lacin Idil (TAYLOR & FRANCIS INC, 2022)
More than 200 million girls and women today are estimated to have gone through female genital mutilation (FGM). In this study, I make a novel contribution to the global literature on FGM by examining domestic resistance to the anti-FGM norm in the context of norm diffusion processes. I provide a novel theoretical perspective to the study of FGM by introducing a compromise-building approach. According to this approach, strong local resistance to a transnational norm that obligates the removal of harmful traditional practices might motivate some transnational norm advocates to support a compromise solution to minimize harm, leading to normative contestation in the transnational domain. This approach is illustrated by the rise of advocacy for medicalized and minor forms of FGM as a harm reduction strategy as a result of the continuation of traditional forms of FGM. The compromise-building approach also brings a new theoretical perspective to the literature on norm diffusion.
Keywords: INTERNATIONAL NORMS; WOMENS RIGHTS; POLICY; RISK; SOCIALIZATION; CONTESTATION; STATEMENT; KNOWLEDGE; DYNAMICS; Public, Environmental & Occupational Health; Women's Studies